2014
DOI: 10.1371/journal.pone.0087401
|View full text |Cite
|
Sign up to set email alerts
|

Ultraweak Photon Emission as a Non-Invasive Health Assessment: A Systematic Review

Abstract: We conducted a systematic review (SR) of the peer reviewed scientific literature on ultraweak photon emissions (UPE) from humans. The question was: Can ultraweak photon emissions from humans be used as a non-invasive health assessment? A systematic search was conducted across eight relevant databases: PubMed/MEDLINE, BIOSIS, CINAHL, PSYCHINFO, All of Cochrane EBM databases, GIDEON, DoD Biomedical Research, and clinicaltrials.gov from database inception to October 2011. Of the 1315 studies captured by the searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 82 publications
0
41
0
Order By: Relevance
“…41 43,31 In further advances, the technique has been expanded to include visualization of spontaneous photon emission in microbial and animal cells, and also live animals and in humans. 44,45 Hence, the technique requires attention to the types of ROS one is trying to measure, and the types of filters used. Importantly, the delayed fluorescence of chlorophyll, and the reaction of radical carbonyl groups with chlorophyll, can cause possible confounding factors in the data analysis and necessitates pre-incubation in the dark to allow for relaxation of the chlorophyll fluorescence.…”
Section: Ultra-weak Photon Emissionmentioning
confidence: 99%
“…41 43,31 In further advances, the technique has been expanded to include visualization of spontaneous photon emission in microbial and animal cells, and also live animals and in humans. 44,45 Hence, the technique requires attention to the types of ROS one is trying to measure, and the types of filters used. Importantly, the delayed fluorescence of chlorophyll, and the reaction of radical carbonyl groups with chlorophyll, can cause possible confounding factors in the data analysis and necessitates pre-incubation in the dark to allow for relaxation of the chlorophyll fluorescence.…”
Section: Ultra-weak Photon Emissionmentioning
confidence: 99%
“…The feasibility of recording UPE as a tool for measuring dynamic changes in human health and various physiological conditions has been reported (Bajpai et al, 2013; van Wijk, 2014; Van Wijk et al, 2014) and was reviewed recently (Ives et al, 2014). For example, a wide diversity of conditions are associated with changes in the UPE profile, including aging (Sauermann et al, 1999), diurnal biological rhythms (Cohen and Popp, 1997; Wijk E. P. and Wijk R. V, 2005; Cifra et al, 2007; Van Wijk et al, 2007; Kobayashi et al, 2009), and conscious activities (Van Wijk et al, 2005, 2006, 2008).…”
Section: Moving Toward a New Visionmentioning
confidence: 99%
“…Assessment of biophotonic activity shows promise as a diagnostic tool within the Western medical model (Brownstein et al, 2007;Ives et al, 2014), with significant differences in photon emission patterns having been found between healthy and diseased organisms (van Wijk & van Wijk, 2005). Differences in biophoton emission rates also appear between groups of healthy cells and cancer cells, with increasing emission rates correlated with increasing malignancy of tumor cells (Popp, 2009;Schamhart & van Wijk, 1987;Scholz, Staszkiewicz, Popp, & Nagl, 1988).…”
Section: International Journal Of Transpersonal Studies 137mentioning
confidence: 99%